PROGRAM MANAGEMENT OF STUDENT CADRE DEVELOPMENT AND ITS IMPACT ON STUDENT RESILIENCE - Fransiskus Sawan; Benediktus Risaldo Baeng; Christian Arje Antas (Program Studi PGSD Universitas Flores, 2026)
Higher education institutions are expected to produce graduates who excel not only academically but also in non-academic competencies. Among these competencies, resilience is increasingly recognized as a strategic soft skill for coping with academic, social, and personal pressures. This study aimed to examine the effectiveness of managing the Synergoi Paulus Cadre Development Program in enhancing student resilience at Universitas Katolik Indonesia Santu Paulus Ruteng. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were collected using a one-group pretest–posttest survey involving 40 students who participated in a 21-day intensive residential cadre program, followed by monthly reinforcement sessions. The instrument was an 18-item Likert-scale questionnaire measuring six resilience indicators: emotional regulation, adaptability, self-confidence, social support, persistence (adversity quotient), and problem-solving skills (Cronbach’s Alpha = 0.873). Quantitative data were analyzed using descriptive statistics, paired-samples t-test, Cohen’s d effect size, and 95% confidence intervals. Qualitative data were obtained through structured experience-sharing sessions and were analyzed thematically. The results indicated significant improvements across all resilience indicators (p<0.001) with large effect sizes. These findings confirm that a structured, values-based, and systematically evaluated student development program management approach is effective in strengthening student resilience.